Toxicity Mechanisms of Mixtures of Anionic and Non-Ionic Surfactants - Francisco Ríos; Manuela Lechuga; Ana Isabel García-López; José María Vicaria-Rivillas; Germán Luzón (Proceedings)
In recent years, several toxicological studies concerning pollutants have focused on the joint toxicological assessment of co-pollutants, revealing that multiple interactions between toxics can appear and need to be described [...]